2002
DOI: 10.1016/s0045-6535(01)00086-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of reactive dyestuffs, auxiliaries and selected effluents in textile finishing industry to luminescent bacteria Vibrio fischeri

Abstract: The toxicity of 17 selected process e uents, 11 reactive dyestu s and 8 auxiliaries from a textile dyeing and ®nishing mill in Ayazaga, Istanbul, Turkey was evaluated by bioluminescence test using bacteria Vibrio ®scheri in LUMIStox 300. The EC 20 and EC 50 for auxiliaries, the EC 20 for dyestu s were determined. For selected process e uents GLvalues, the dilution level at which a wastewater sample causes less than 20% inhibition, were examined. Our results demonstrate that the toxicity assessment with lumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
0
15

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(126 citation statements)
references
References 20 publications
1
110
0
15
Order By: Relevance
“…Our previous investigations indicated that the first by-products after short-term ozonation are not to be underestimated since they might have higher toxic potential than their original compounds (Wang et al, 2002). In the present study a commonly used azo reactive dye, Remazol Black 5 was chosen as a representative model compound to obtain detailed information on the degradation products during various ozonation period and to evaluate their potential toxic effect on microorganisms and rat hepatoma cells by applying BOD 28 biological degradation test, and two toxicity assays namely the bioluminescence test and the neutral red (NR) cytotoxicity test.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous investigations indicated that the first by-products after short-term ozonation are not to be underestimated since they might have higher toxic potential than their original compounds (Wang et al, 2002). In the present study a commonly used azo reactive dye, Remazol Black 5 was chosen as a representative model compound to obtain detailed information on the degradation products during various ozonation period and to evaluate their potential toxic effect on microorganisms and rat hepatoma cells by applying BOD 28 biological degradation test, and two toxicity assays namely the bioluminescence test and the neutral red (NR) cytotoxicity test.…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3, and in Table 1. Values of percentage inhibition of relative luminescence above 0.2 were assumed as toxic effects to V. fischeri (Wang et al 2002), as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…The wet processes include scouring, singeing and dyeing which use a large amount of water. Among this process dyeing requires immense amount of water which involves changing the color of the textile spun (Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%